PENDAMPINGAN OPTIMALISASI MANAJEMEN KURIKULUM MELALUI BLENDED LEARNING DI ERA DIGITAL - Puput Anggraini; Imam Khaudli (LPPM STAI Muhammadiyah Probolinggo, 2025)
This study aims to describe and analyze how blended learning is implemented in curriculum management to answer the challenges of education in the digital era. The approach used is qualitative, with a case study type at SMK Darussalam. Data collection techniques were carried out through in-depth interviews, participatory observation, and documentation, involving 11 key informants: the principal, vice principal of curriculum, teachers, business personnel, and students. Data were analyzed using the Miles & Huberman model, which includes data reduction, data presentation, and verification. The analysis methods used include content analysis, discourse analysis, and interpretative analysis, while data validity is maintained through triangulation of sources and techniques, and member checks. The results of the study indicate that blended learning encourages digital transformation of schools, strengthens learning flexibility, and increases student participation in learning. The contribution of this study lies in mapping the implementation strategy of blended learning within the framework of technology-based school curriculum management.